MULTIPLE HOMES AND UNHOMELY BELONGING - Anne Holden Rønning (Le Simplegadi, 2016)
In a society where migration plays a significant role our identities become ambivalent to ourselves and only partly legible to others. This article reflects on the role of the written word, political, social, and literary, as a narrative of multiple homes. Among the issues which determine the discourses and narratives of ‘multiple homes’ and ‘unhomely belonging’ are language and language politics (situational or real), beliefs about identities as solid and identifiable, constant border-crossings as central to many people’s lives, and the collision of social and cultural codes in the meanings and practices assigned to ‘the foreigner’.